COMMUNITY HEALTH INFORMATION-SHARING BY LATINO PALLIATIVE CARE LAY ADVISORS - Felts , Jenna (East Carolina University, 2022)
Lay health advisors are an evidence-based intervention that can address health equity. Lay advisors are trusted members of the community and serve as natural helpers. With training, lay advisors can help others navigate the health care system. The purpose of this study was to understand how trained Latino palliative care lay advisors (PCLAs) record information sharing with community-dwelling Latino adults with a cancer diagnosis. A mixed-methods community-based action design, guided by the Ethno-Cultural Gerontological Model, was conducted between 2020 and 2021. This project trained 15 Latino lay advisors in palliative care principles. Following training, PCLAs were assigned Latino adults with a cancer diagnosis to contact via telephone and share information about home symptom management and advance care planning. Encounter forms were the source of documentation used by the PCLAs following their telephone discussions. A total of 41 Latino adults with cancer agreed to participate in the telephone intervention. PCLAs contacted 85.3% (35/41) of the participants with information regarding home symptom management and advanced care planning. Less than half of the sample (n=17; 48.5%) reported having one or more symptoms on the day of the call. Physical symptoms (i.e., pain and tiredness) were more prevalent than emotional symptoms (anxiety and depression). Lay advisors documented information shared on advance care planning with 74.2% (n=26) of participants. Trained lay advisors attempted several telephone calls before participants answered their call. When contacts were made, participants and PCLAs reported that the encounter was helpful. Over one third (35.2%) of participants did not receive information on advance care planning. Advance care planning remains a difficult topic to discuss. Interactive games, such as the “Hello Game,” might assist Latino communities with these conversations. Future training might include best practice in recording information sharing.
Keywords: Community Nursing; Latino Palliative Care; Documentation